Hypoxia-inducible Factor α Subunit Stabilization by NEDD8 Conjugation Is Reactive Oxygen Species-dependent - Ryu, Ji-Hye (American Society for Biochemistry and Molecular Biology, 2011)
Hypoxia-inducible factor α proteins (HIF-αs) are regulated oxygen dependently and transactivate numerous genes essential for cellular adaptation to hypoxia. NEDD8, a member of the ubiquitin-like family, covalently binds to its substrate proteins, and thus, regulates their stabilities and functions. In the present study, we examined the possibility that the HIF signaling is regulated by the neddylation. HIF-1α expression and activity were inhibited by knocking down APPBP1 E1 enzyme for NEDD8 conjugation but enhanced by ectopically expressing NEDD8. HIF-1α and HIF-2α were identified to be covalently modified by NEDD8. NEDD8 stabilized HIF-1α even in normoxia and further increased its level in hypoxia, which also occurred in von Hippel-Lindau (VHL) protein- or p53-null cell lines. The HIF-1α-stabilizing effect of NEDD8 was diminished by antioxidants and mitochondrial respiratory chain blockers. This suggests that the NEDD8 effect is concerned with reactive oxygen species driven from mitochondria rather than with the prolyl hydroxylase (PHD)/VHL-dependent oxygen-sensing system. Based on these findings, we propose that NEDD8 is an ancillary player to regulate the stability of HIF-1α. Furthermore, given the positive role played by HIF-αs in cancer promotion, the NEDD8 conjugation process could be a potential target for cancer therapy.